THE USE OF KONDORSKY STRESS THEORY TO PREDICTION OF THE COERCIVE FORCE OF IRON POWDER - Котвицька, Клавдія (SWorldJournal, 2024)
The article examines the effect of increasing the internal stress in iron powder on its coercive force. A model describing this dependence was developed and used to predict the coercive force of other samples. The internal stresses were created by a ball